Diversity and uniformity in economic theory as an explanation of the recent economic crisis - Jan Kregel (Levy Economics Institute of Bard College, 2012)
Market economies and command economies have long been differentiated by the presence of alternative choice in the form of diversity. Yet most mainstream economic theory is premised on the existence of uniformity. This paper develops the implications of this contradiction for the theory of prices, income creation, and the analysis of the recent financial crisis, and provides a critique of traditional theory from an institutionalist perspective developed by J. Fagg Foster.
Keywords: B0; D01; D41; E01; E31; P00; 330; Financial Crisis; W. Petty; Markets; Equilibrium Prices; Financial Crisis